Happy Lane Sdn. Bhd. / Mohd Azamin Ahmad Adli ... [et al.] - Ahmad Adli, Mohd Azamin; Ani, Rossfulnizam; Ibrahim, Abdul Razak; Kamis, Mazleya; Ali, Mohd Amran (2000)
Happy Lane Sdn. Bhd was established for the purpose of bowling services. This company is offer facilities of new era for bowling sport entertainment. Besides, it could help to provide employment opportunities. This company based at Sungai Petani, kedah.